School commitment and alcohol use: The moderating role of race and ethnicity. - Tamela McNulty Eitle; David James Eitle (Education Policy Analysis Archives, 2007)
Research indicates that lower levels of school commitment may be one potential outcome of policy initiatives such as high-stakes testing and exit exams. Such outcomes may lead these policy initiatives to have unintended consequences for students, particularly racial or ethnic minority students. This study examines whether race or ethnicity moderate the relationship between school commitment and alcohol use or binge drinking among a sample of Florida public middle and high-school students who were surveyed as part of the 2002 Florida Youth Substance Abuse Survey. Low school commitment was found to be associated with a greater likelihood of alcohol use in the past 30 days and a greater likelihood of binge drinking during the past two weeks for Black, Hispanic, and White students. Both the higher average levels of school commitment among Black and Hispanic than among white students and the greater association between low school commitment and the two alcohol use outcomes for Black and Hispanic students compared to White students account for some of the difference in alcohol use and binge drinking among the different groups. 1 Financial assistance for this study was provided by the National Institute on Alcohol Abuse and Alcoholism (grant number R01 AA13167) and the National Institute of Drug Abuse (grant number R01 DA018645-01A1). We gratefully acknowledge Michael French and members of the Health Economics Research Group (HERG) for their research suggestions and William Russell for editorial assistance. The authors are entirely responsible for the research and results reported in this paper, and their position or opinions do not necessarily represent those of NIAAA or NIDA.